The Effect of Experiential Marketing and Brand Image on Purchase Decisions Through Word of Mouth as Intervening Variables: Pengaruh Experiential Marketing Dan Brand Image Terhadap Purchase Decision Melalui Word Of Mouth Sebagai Variabel Intervening - Fatchiyah, Alifatul; Sukmono, Rita Ambarwati (Indonesian Journal of Innovation Studies, 2021)
This study aims to determine the effect of Experiential Marketing (X1) and Brand Image (X2) variables on Purchase Decision (Y) through Word Of Mouth (Z) as Intervening Variables. This research was conducted at LKP Modes Aniq Sidoarjo. This study uses a survey method where the primary data is obtained from a questionnaire. The sample is a resident of Modes Aniq who is taken randomly as many as 100 respondents. Data analysis method using PLS (Partial Least Square) using smart PLS software version 3.0. The results showed that Experiential Marketing had a positive and significant effect on Purchase Decision. Experiential Marketing has a positive and significant effect on Word Of Mouth. Brand Image has a positive and significant effect on Purchase Decision. Brand Image has a positive and significant effect on Word Of Mouth. Word of Mouth has a positive and significant effect on Purchase Decision. Experiential Marketing indirectly has a positive and significant effect on Purchase Decision through Word Of Mouth as an Intervening variable. Brand Image indirectly has a positive and significant effect on Purchase Decision through Word Of Mouth as an Intervening variable. Keywords: Experiential Marketing, Brand Image, Word Of Mouth and Purchase Decision.